Fluid Dynamic Assessment of Tall Buildings with a Variety of Complicated Geometries - Rahul Kumar Meena; Ritu Raj; S. Anbukumar; Mohammad Iqbal Khan; Jamal M. Khatib (Buildings)
The exponential increase in population has led to a shortage of land for constructing tall buildings, resulting in the need to design irregular structures due to the limited availability of land. Assessing the impact of wind-generated effects can be achieved utilizing the Computational Fluid Dynamics (CFD) method, specifically employing ANSYS. This involves resolving the intricate fluid dynamics problem through numerical analysis using the ANSYS software. The validation study is performed on a standard shape-building model where the result is compared with experimental values and other international standards. The outcomes are presented in a graphical format, such as mean pressure, streamline, and pressure distribution in the vertical and horizontal planes. This research has studied four building models with equal area and height. Models A and B have regular shapes, while Models C and D exhibit an irregular ‘Y’ shape. The wind incidence angle was adjusted between 0 and 180 degrees at every 15-degree interval. The results were validated to ensure the accuracy of the numerical techniques employed. This involved performing validation and grid sensitivity analyses, which showed consistent results comparable to experimental data and established international standards. Model-C irregular-shaped buildings demonstrated the highest efficiency in minimizing wind loads among the building models examined in this study.